Regulatory B cells in ANCA-associated vasculitis. Issue 8 (10th May 2013) - Wilde, B; Thewissen, M; Damoiseaux, J; Knippenberg, S; Hilhorst, M; van Paassen, P; Witzke, O; Cohen Tervaert, J W
Abstract : Objectives: B cells have immunoregulatory function acting as antigen-presenting cells. A separate subset of interleukin (IL)-10 producing B cells (Breg) regulating T cell mediated immunity has been identified. In the present study, we investigated the role of Breg in antineutrophil cytoplasmic antibodies-associated vasculitis (AAV). Methods: 17 healthy controls (HCs) and 41 patients with AAV were enrolled. 30 patients with AAV were in remission. Furthermore, 11 patients with AAV with active disease were studied. Breg were defined as IL-10 + CD19 + B cells upon culture with cytosine-phosphate-guanosine oligodeoxynucleotide (CpG ODN) 2006. Next to Breg, CD4 + CD127 low CD25 hi CD39 neg /CD39 + regulatory T-cells (Treg), interferon (IFN)γ +, IL-4 + and Il-17A + T helper cell subsets were determined via flow cytometry. Results: Patients with active or quiescent disease showed a diminished fraction of Breg as compared with HCs. The frequency of IFNγ + T helper cells was negatively associated with Breg in untreated AAV in remission but not in active vasculitis or in HCs. Interestingly, the total Treg population and the CD39 + Treg subpopulation correlated positively with Breg in inactive patients with AAV. Conclusions: IL-10 producing B cells are diminished in AAV. Furthermore, Breg might regulate Th1 cells and are associated with Treg in quiescent AAV. Suppression of Th1 cells by Breg may be insufficient in active AAV.